2016
DOI: 10.1073/pnas.1607500113
|View full text |Cite
|
Sign up to set email alerts
|

Computational investigation of cold denaturation in the Trp-cage miniprotein

Abstract: The functional native states of globular proteins become unstable at low temperatures, resulting in cold unfolding and impairment of normal biological function. Fundamental understanding of this phenomenon is essential to rationalizing the evolution of freeze-tolerant organisms and developing improved strategies for long-term preservation of biological materials. We present fully atomistic simulations of cold denaturation of an α-helical protein, the widely studied Trp-cage miniprotein. In contrast to the sign… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

21
69
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 50 publications
(91 citation statements)
references
References 74 publications
21
69
1
Order By: Relevance
“…7). This is consistent with (20), in which it is suggested that the hydrophilic residues make increased hydrogen bonds with water molecules at lower temperature, which is counted as a major driving force of cold denature.…”
Section: Interprotein Interfacesupporting
confidence: 90%
See 3 more Smart Citations
“…7). This is consistent with (20), in which it is suggested that the hydrophilic residues make increased hydrogen bonds with water molecules at lower temperature, which is counted as a major driving force of cold denature.…”
Section: Interprotein Interfacesupporting
confidence: 90%
“…9), suggesting that at low temperatures, the fluctuation of biological importance is hindered. In the crystal structure of apo form studied at room temperature at a resolution of 2.3 Å (PDB: 5DFR), some residues of Met20 loop (residues [16][17][18][19][20] were missing, and others (residues 21-24) were weak or partially disordered with high B factor (40-50 Å 2 ) (31), suggesting a large fluctuation in accord with our simulations. The conformational variations are visualized in Fig.…”
Section: Met20 Loop Structuresupporting
confidence: 75%
See 2 more Smart Citations
“…As a matter of fact, many life forms survive under extreme T-P conditions [1,2], implying that their proteins fit that environment. Recent works [3][4][5][6][7][8][9][10] have evidenced that changes in T and P significantly alter the water-mediated hydrophilic and hydrophobic interactions of the residues along the chain, with an effect that depends on the sequence. However, a direct observation of how the protein selection responds to extreme changes in the aqueous conditions is still lacking.…”
Section: Introductionmentioning
confidence: 99%